AN INVESTIGATION OF THE EFFECTS OF READ 180® ON FOURTH GRADE READING ACHIEVEMENT AND HOW SELECTED TEACHERS IMPLEMENT THE PROGRAM - Hubbard, Anne Judith (2011)
This study examined the effects of the READ 180 ®® program on the reading achievement levels of fourth grade students who participated in the READ 180 ®® program (Scholastic Incorporated, 2005) compared to fourth grade students who were reading below grade level but who were not participating in the READ 180 ®® program. The study compared the Scholastic Reading Inventory (SRI) scores of each group administered in September 2009 and May or June 2010. The mean reading achievement gain for each group was compared to determine if there was a significant difference between the reading scores. Results of the One-Way ANCOVA yielded no significant statistical differences, at the probability level ( p level) of .05, in the posttest SRI reading score means for students in READ 180 ®® and non- READ 180 ®® reading programs, after controlling for initial differences on the pretest SRI scores. However, if the probability was set for p =< .10, the results of the study would demonstrate a statistically significant difference between the posttest SRI scores. Although there was evidence READ 180 ®® was statistically significant and beneficial to students, the results are not conclusive. The results of the Two-Way ANCOVA showed no significance of interaction between reading program status and TerraNova Third Edition TM qualification criteria on posttest reading scores. The study also investigated whether teachers supplemented the standard READ 180 ®® program with other reading interventions, activities, and modifications based upon the needs of the students. Teachers who taught READ 180 ®® and special education teachers who assisted with READ 180 ®® implementation were surveyed using a web-based survey program. Survey results indicated teachers supplemented the standard READ 180 ®® program including Whole Group, Small Group, and Independent Reading Group rotations with reading interventions, activities, and modifications based upon the needs of the students. Supplementary activities included the use of Internet resources, ...